UNDERSTANDING INDONESIAN NEWS MEDIA CULTURE IN REPRESENTING DIVISIVE ISSUES - Prayudi Prayudi (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2015)
This research looks at the culture (daily practice) that Indonesian news media has to follow in representing divisive issues. Mass media and divisive issues are inseparable. The representation of divisive issues in the Indonesian news media is the result of a complex construction process which incorporates cultural, political economic and industrial factors. Particularly, it is very much influenced by the rise of the idea of civil society. It has also driven the new idea of freedom of the press in Indonesia. The press becomes more critical in reporting an issue. Media policies also experienced significant changes. Government communication policy only regulates the press in order to ensure they obey codes of ethics and law. To this extent, controversial and highly divisive issues are managed and represented according to the internal policies of the media organizations, rather than the directives of government. At the same time, the mass media has to consider various factors in reporting sensitive and potentially divisive issue. In this research, in-depth interview was conducted to some Indonesian news media editors and journalists to understand how the media develop their editorial policies and what need to be considered in reporting divisive issues. Further, some news of divisive issues were analyzed to identify how cultural, political economic and social conditions are treated differently in constructing news.